The Implementation of Extracuricular Activities of Adolescents Scientific Paper Based on Character Education - Fetrimen Fetrimen; Yuni Yulianti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to determine the validity of the gap between madrasah policies and field facts in implementing extracurricular activities based on character education. Novelty by using the Discrepancy Evaluation Model (DEM) framework which is estimated to have the accuracy of assessing extracurricular activities of Adolescent Scientific Work based on character education as a basis for evaluating success. This research was conducted at Madrasah Aliyah Negeri (MAN) 5 Bogor. This data was obtained from research subjects such as madrasah heads, student affairs representatives, coaches, chairmen, and parents. Data were collected from the triangulation process by observation, interviews, and documentation studies and then analyzed the findings data in accordance with the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 62 of 2014 concerning Extracurricular Activities and Guidelines for Extracurricular Activities in Primary and Secondary Education as the evaluation standards used. The results of the study have an impact on the need for improvement in extracurricular activity programs because there is a gap between Madrasah stakeholder policies and field facts, namely the lack of optimal management, management and guidance of KIR Coaches, as well as financing and infrastructure in supporting extracurricular activities